GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Systematic review update of organisational-level mental health promotion interventions: evidence from healthcare, construction, and telework-based mobile work settings - Eleftherios Giovanis; Oznur Ozdamar; Birgit Aust; Johanna Cresswell-Smith; Arlinda Cerga Pashoja; Caleb Leduc; Andrea Sinesi; Carolina Piña; Chantal Van Audenhove; Gentiana Qirjako; Victoria Ross; Margaret Kenneally; et al. (International Archives of Occupational and Environmental Health, 2026)

Boar sperm capacitation status as predictor of IVF cleavage rate - Isabel Rodriguez; Alexandra Keller; Lindsey Jennett; Megan Johnson; Ian Shofner; Tyler Weide; Kourtney Jimmerson; Bethany Redel; Karl Kerns (Animal Reproduction Science, 2025)

Analyse humaner Hirnorganoide vom Millimeter- bis zum Nanometerbreich - Juan Eduardo Rodriguez-Gatica; Vira Iefremova; Oliver Brüstle; Martin Karl Schwarz; Ulrich Kubitscheck (BIOspektrum, 2023)
We combine tissue expansion and light sheet fluorescence microscopy to analyze brain organoids. It is possible to zoom from a mesoscopic overview to super-resolution in a single imaging session, revealing cellular and subcellular structural details, such as the positions and spacing of pre- and postsynaptic proteins. Light sheet fluorescence expansion microscopy (LSFEM) greatly facilitates the qualitative and quantitative use of organoids in developmental and disease-related studies.

Correction to: Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Rastogi; Sunny Nguyen; et al. (GeroScience, 2022)

Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Ragosti; Sunny Nguyen; et al. (GeroScience, 2021)

Superoxide-mediated oxidative stress accelerates skeletal muscle atrophy by synchronous activation of proteolytic systems - Young C. Jang; Karl Rodriguez; Michael S. Lustgarten; Florian L. Muller; Arunabh Bhattacharya; Anson Pierce; Jeongmoon J. Choi; Nan Hee Lee; Asish Chaudhuri; Arlan G. Richardson; Holly Van Remmen (GeroScience, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Effects of Upstream Diversion of Colorado River Water on the Estuarine Bivalve Mollusc Mulinia coloradoensis - Carlie A. Rodriguez; Karl W. Flessa; David L. Dettman (Conservation Biology, 2001)
The Colorado River of the United States and Mexico is extensively dammed and diverted; only a fraction of its previous flow still reaches its estuary. How has the lack of freshwater inflow affected the estuary's biota? Because no prediversion studies are available for comparison, we examined the composition and geochemistry of subfossil shells dating from before the Colorado's diversion. The bivalve mollusc Mulinia coloradoensis was once the most abundant species of clam inhabiting the Colorado Delta. Today, however, only a small population survives near the mouth of the river. The relative abundance of empty shells of this species decreases with increasing distance from the mouth of the Colorado River, indicating that M. coloradoensis was dependent on the flow of the river. The δ 18 O values in shells of subfossil M. coloradoensis are significantly more negative than δ 18 O values in live‐collected shells of Chione fluctifraga , the most common bivalve living on the delta today. This indicates that M. coloradoensis lived in water lower in salinity than is now typical of the delta. The decline in abundance of M. coloradoensis is most likely due to the post–1930 decrease in flow of Colorado River water to its estuary. Paleontological and geochemical analyses of subfossils can provide environmental baselines for communities that existed prior to human alteration of the habitat.

Effects of Upstream Diversion of Colorado River Water on the Estuarine Bivalve Mollusc Mulinia coloradoensis - Carlie A. Rodriguez; Karl W. Flessa; David L. Dettman (Conservation Biology, 2001)